Tikhonov and Landweber convergence rates: characterization by interpolation spaces. (15th September 2015) - Andreev, R
Abstract: Algebraic convergences rates of (iterated) Tikhonov regularization for linear inverse problems in Hilbert spaces are characterized by the membership of the exact solution to intermediate spaces produced by the K-method of real interpolation. Similar results are obtained for the Landweber iteration.